Green Human Resource Management: An Analysis of Role of Public Sector in Climate Action & in Achieving SDG 13 in India (Indian Journal of Management and Language (IJML), 2026)
The growing threat of climate change has prompted organisations worldwide to integrate sustainability into their operations and human resources practices. This study empirically examines the role of Green Human Resource Management (GHRM) in promoting climate action (SDG 13) within India’s public-sector organisations. The research investigates how green HR practices, such as green recruitment, training, performance appraisal, and employee engagement, contribute to enhancing environmental awareness, sustainable work behaviour, and institutional commitment to carbon reduction and resource conservation. A mixed-methods empirical approach has been adopted, combining survey data from employees across selected public-sector enterprises with in-depth interviews with Human Resources (HR) and sustainability officers. Quantitative analysis will test the relationships between GHRM practices and climate action outcomes using statistical modelling, while qualitative insights will explore implementation challenges and organizational culture factors. Findings have highlighted the critical role of public sector organisations in driving climate action through effective HR interventions, policy alignment, and leadership commitment. The study offers policy recommendations for integrating GHRM into national sustainability strategies and contributes to the broader discourse on achieving SDG 13: Climate Action through human resource innovation in India.